Islamic and Civilized: Refusals of ‘Othered’ Sudanese Portrayed in “The Museum” Written by Leila Aboulela - Shofah, Novia Adibatus; Pitaloka, Diah; Andini, Kekeh Dwita (Proceedings of International Conference on Islamic Civilization and Humanities, 2023)
A Sudanese woman named Shadia is described as Islamic and civilized in the short story “The Museum” by Leila Aboulela. Shadia shows herself as a Muslim who migrated from Sudan to Scotland and is described as a civilized Muslim. There are indications that the short story has implicit messages showing refusals to the ‘othered’ Sudanese as a third-world country. Therefore, this study aims to describe how the refusals of ‘othered’ Sudanese is seen through Islamic woman and civilized Sudan, which is more civilized than the view from the West. This research studies postcolonialism from Edward Said’s perspective because it discusses the labels given to Eastern and Western countries. The results of this study show that Shadia, as a Sudanese Muslim, can strengthen Islamic principles as an aspect of majesty and civilization. She also can explicitly express her opinion as an independent Muslim woman who refuses European-centric understanding as the ‘other,’ as the ‘Orient,’ and as primitive.